Pengaruh Gerakan Literasi Sekolah Terhadap Kemampuan Membaca Siswa Di SD Al-Irsyad Kota Sorong - Sri Puput Wijayanti; Mulyono Mulyono (MISOOL: Jurnal Pendidikan Dasar, 2020)
This study aims to determine: 1) the implementation of the school literacy movement; 2) determine students' reading ability after the school literacy movement is held; 3) the influence of the school literacy movement on students' reading ability. This study uses a quantitative approach to the type of survey research. The population of all students in grade 3 SD Al Irsyad, Sorong City. The sampling technique used a saturated sample by making the entire population the research sample. The data was collected by providing analysis and tests through google forms, then analyzed using simple linear regression test statistics. The results showed that: 1) the implementation of the school literacy movement at SD Al-Irsyad Sorong City was in the high category (74%); 2) the reading ability of grade 3 students at SD Al-Irsyad, Sorong City is in the high category (71%); 3) the school literacy movement has a positive and significant effect on the reading ability of 3rd graders at Al-Irsyad Elementary School, Sorong City. In conclusion, the school literacy movement at SD AL-Irsyad can improve students' reading skills